2011
DOI: 10.1111/j.1365-2141.2011.08670.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myeloid leukaemia and sickle cell disease: could imatinib prevent vaso‐occlusive crisis?

Abstract: We report the case of a patient with homozygous sickle cell disease (SCD) and chronic myeloid leukaemia (CML) whose vaso-occlusive crises were resolved with imatinib therapy.The patient, born in 1983, underwent a splenectomy at the age of 7 years for acute splenic sequestration. Hospitalization for vaso-occlusive crisis (VOC) occurred about once a year until 2007. The patient was never treated with hydroxycarbamide. In 2008, the patient was hospitalized five times for bone VOC with high fever (40°C) but no cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…The present case series suggests for the first time the presence of MCAS as a factor in the morbidity of poor-phenotype SCA. As hypothesized by Vincent et al 9 and others, 45 , 46 several patients in the present series seem to have been significantly helped by therapy targeted at MC mediator production or action. Although it is interesting that current high-end estimates of the portion of the general population harboring MCAS (14%–17%) 41 , 42 roughly correspond to the portion of the SCA population suffering a poor phenotype of SCA, specific prospective studies will be needed to confirm the portion of the SCA population truly harboring MCAS.…”
Section: Discussionsupporting
confidence: 73%
“…The present case series suggests for the first time the presence of MCAS as a factor in the morbidity of poor-phenotype SCA. As hypothesized by Vincent et al 9 and others, 45 , 46 several patients in the present series seem to have been significantly helped by therapy targeted at MC mediator production or action. Although it is interesting that current high-end estimates of the portion of the general population harboring MCAS (14%–17%) 41 , 42 roughly correspond to the portion of the SCA population suffering a poor phenotype of SCA, specific prospective studies will be needed to confirm the portion of the SCA population truly harboring MCAS.…”
Section: Discussionsupporting
confidence: 73%
“…Although the evidence is limited, clinical observations support a role for mast cells in chronic and acute pain in SCD. In a case report, a patient with SCD having multiple VOCs per year stopped having VOCs with imatinib treatment . On discontinuation of imatinib, VOCs recurred.…”
Section: Mast Cell Activity In Pain In Sickle Cell Diseasementioning
confidence: 99%
“…The mechanism of mast cell's role in sustained hyperalgesia is based on the studies in sickle mice. However, two separate clinical studies on sickle patients show that the use of imatinib, a known mast cell inhibitor, significantly reduced painful episodes in patients with SCD [ 25 , 26 ]. Another case report showed that a sickle patient who died following an overdose of fentanyl was on fentanyl for more than 18 months and had pruritis and sickle crises type of pain for 2 days as well as ACS and respiratory depression secondary to fentanyl overdose [ 27 ].…”
Section: Complex Pathophysiology Of Scd Is Intertwined With Painmentioning
confidence: 99%